Productivity improvement in poly-cover packing line through line balancing and automation. (2020) - Harikrishnan, R.; Rajeswaran, M.; Sathish Kumar, S.; Dinesh, K.
Abstract: Improving productivity is a popular topic for any kind of company to enrich the income through reduced workload and the development of new strategies for a specific business. Historically Industrial Engineers have a strong concern in Productivity Improvement through Work-Study. It is common and almost has become mandatory in most of the companies to meet the competitive market. Work-study also facilitates various improvements like Waste identification and elimination, Automation, Takt time, Line balancing, etc. which improves the competitive edge of the Organizations in its market. Hence, this study thus allows the bottleneck to be noticed and suggests a suitable system for improving productivity. By applying line balancing and automation in the enterprise at Poly-cover packing line Rs. 7.2 Lakhs per annum for man-power is saved.